Characterization of the electromagnetic parameter uncertainty in single-ply unidirectional carbon-fiber-reinforced-polymer laminas. (1st April 2019) - Riley, Elliot J.; Koudela, Kevin L.; Narayanan, Ram M.
Abstract: This paper characterizes the variation in electromagnetic properties of single-ply unidirectional carbon-fiber-reinforced-polymer (CFRP) laminas between samples fabricated using the same material. The variation is referred to as the electromagnetic-parameter uncertainty (EPU). The resulting EPU from both wet-layup and pre-preg fabrication techniques were investigated. A free-space materials characterization system operating from 4 to 18 GHz was used to characterize the electromagnetic properties with respect to the main fiber direction. A surface-impedance representation was calculated from the measured data to expose the EPU. Finally, the effects of the EPU on the reflectivity properties of electromagnetic-absorber designs using unidirectional CFRP were determined.